2018
DOI: 10.20546/ijcmas.2018.709.119
|View full text |Cite
|
Sign up to set email alerts
|

Stability Analysis for Seed Cotton Yield and its Component Traits in Hybrids of Desi Cotton (G. arboreum L.)

Abstract: Genotype x environment interactions is of major importance to the plant breeder in developing improved genotypes. When genotypes are compared over a series of environments, the relative rankings usually differ. This causes difficulty in demonstrating the significant superiority of any genotype. This interaction is usually present whether the varieties are pure lines, single cross, double cross hybrids, top crosses, S 1 lines or any other material with which the breeder may be working.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…The estimate of GCA and SCA variances was presented in table 1. The results are in concordance with the finding of Punitha and Raveendran (1999), Saravanan et al, (2010), Shinde et al, (2018) Swetha et al (2018 and Chinchane et al (2018) for yield and quality characters. The per se performance was considered as the first important selection index in the choice of parents and the selection of suitable parents with high per se performance will result in superior hybrids (Gilbert, 1958).…”
Section: Resultssupporting
confidence: 92%
“…The estimate of GCA and SCA variances was presented in table 1. The results are in concordance with the finding of Punitha and Raveendran (1999), Saravanan et al, (2010), Shinde et al, (2018) Swetha et al (2018 and Chinchane et al (2018) for yield and quality characters. The per se performance was considered as the first important selection index in the choice of parents and the selection of suitable parents with high per se performance will result in superior hybrids (Gilbert, 1958).…”
Section: Resultssupporting
confidence: 92%
“…This indicated that the environments created by various sowing dates were justified had mostly linear effect. These results are in agreement with the earlier findings of Tuteja et al (2006), Balakrishna et al (2016), Vanisri et al (2016), Jamwal et al (2016, Chinchane et al (2018) and Pinki et al (2018).…”
Section: Vavdiya Et Alsupporting
confidence: 94%
“…In present studies, it was also concluded that high × high, high × low and low × high general combiners performed better in manifestation of specific F 1 hybrids for yield and lint traits. Previous studies also revealed that for getting good cross combination, at least one of the parents should have good GCA effect i.e., high × high, high × low and low × high GCA parents in cotton (Chinchane et al 2018). In past studies, in some cases high × low, low × high and high × high GCA parents showed best performance for majority traits in upland cotton (Panhwar et al 2008;Khan et al 2011Khan et al , 2015Karademir et al 2016).…”
Section: General Combining Abilitymentioning
confidence: 99%